2011
DOI: 10.1002/elps.201000528
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethylcellulose‐graft‐poly(2‐(dimethylamino)ethyl methacrylate) as physically adsorbed coating for protein separation by CE

Abstract: In this work, a novel graft copolymer, hydroxyethylcellulose-graft-poly(2-(dimethylamino)ethyl methacrylate) (HEC-g-PDMAEMA), used as physical coatings of the bare fused-silica capillaries, was synthesized by using ceric ammonium nitrate initiator in aqueous nitric acid solution. EOF measurement results showed that the synthesized HEC-g-PDMAEMA graft copolymer-coated capillary in this paper could suppress EOF effectively compared to the bare fused-silica capillary, and efficient separations of basic proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 114 publications
2
28
0
Order By: Relevance
“…The main constituent of proteins from egg white is ovalbumin (54%), conalbumin (12%), ovomucoid (11%), ovomucin (3.5%), lysozyme (3.4%), ovoinhibitor (1.5%), ovoflavoprotein (0.8%), ovomacroglobulin (0.5%), avidin (0.5%), among smaller fractions of other proteins [46,47]. The content of conalbumin and ovalbumin were similar to our previous work (conalbumin and ovalbumin were 11.511 and 65.383 mg/mL, respectively [33]). The results demonstrated that the QDED-1 coating was suitable for analysis of biosamples.…”
Section: Separation Of Proteins From Egg Whitesupporting
confidence: 87%
See 2 more Smart Citations
“…The main constituent of proteins from egg white is ovalbumin (54%), conalbumin (12%), ovomucoid (11%), ovomucin (3.5%), lysozyme (3.4%), ovoinhibitor (1.5%), ovoflavoprotein (0.8%), ovomacroglobulin (0.5%), avidin (0.5%), among smaller fractions of other proteins [46,47]. The content of conalbumin and ovalbumin were similar to our previous work (conalbumin and ovalbumin were 11.511 and 65.383 mg/mL, respectively [33]). The results demonstrated that the QDED-1 coating was suitable for analysis of biosamples.…”
Section: Separation Of Proteins From Egg Whitesupporting
confidence: 87%
“…QDED was different from P (VP-co-DMAEMA) [28] and HEC-g-PDMAEMA [33], because the weak positively charged amine groups in PDMAEMA block were quaternized to take with positive charges not only in acid solution, but also in alkaline solution, therefore the chain backbone of quaternized PDMAEMA block strongly adsorbed onto the capillary surface through electrostatic interactions. However, P(VPco-DMAEMA) and HEC-g-PDMAEMA were pH-sensitive polymers, the net positive charges were decreasing with the increasing of pH value.…”
Section: Suppression Of Eof At Different Ph Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharides are also attractive candidates for dynamic coatings for protein separations because they are non-toxic, readily abundant, and biocompatible [1921]. Two novel dynamic coatings based on the chemical substitutions of cellulose have recently been reported [22, 23].…”
Section: Techniquesmentioning
confidence: 99%
“…On the basis of the abundant reactive hydroxyl groups on HEC, HEC can be easily modified through its graft polymerization with hydrophilic vinyl monomers to derive new materials with improved properties 13. Partly HEC grafting copolymers have been used as physical coating in fused‐silica capillary inner wall for protein separation, such as HEC‐ g ‐PDMA (poly ( N, N ‐dimethylacrylamide),14 HEC‐ g ‐PDMAEMA (poly (2‐(dimethylamino) ethyl methacrylate),15 HEC‐ g ‐P4VP (poly (4‐vinylpyridine)) 16. HEC can tightly adsorb onto the fused‐silica capillary inner wall, however, resisting protein adsorption ability of HEC is not very well, comparing to another antifouling polymer PEG (poly (ethylene glycol)).…”
Section: Introductionmentioning
confidence: 99%